The Effect of Stress on the Skin Welfare of Lumpfish (Cyclopterus lumpus Linnaeus, 1758) Broodstock - Thor Magne Jonassen; Albert Kjartan Dagbjartarson Imsland; Karin Pittman (Animals)
The aim of this study was to build on the work already conducted in optimising lumpfish broodstock temperature, photoperiod and nutrition by providing vital information on the stress relationship between mucosal barrier functions and the sexual development of lumpfish broodstock. From a population of approx. 300 fish of 1587 g (SEM ± 704 g), a sub-population of 20 fish was injected with 30 mg/kg fish cortisol implants on 5 January 2018. The control group was not treated with implants. The stress-induced cortisol implant group showed elevated plasma cortisol over a period of approximately one month. Analyses of mucus cell area and density suggested that induced stress could produce a positive functional response (stimulus) in lumpfish early in the experiment through a gentle increase in the barrier strength of the skin, reduced mucus cell size and increased density of mucous cells, resulting in a strengthening of the respiratory capacity of the gills. Mucous cell density and calculated barrier strength in the skin were significantly negatively correlated with plasma cortisol, while in the gill filaments of females, there was a significant negative correlation between mucous cell density and oestrogen levels. The reduced density of “empty” cells (Q cells) after stress induction indicates that these cells are important for the maintenance of homeostasis (physiological equilibrium). The fish in this experiment were considered more robust compared to previous analyses on smaller lumpfish.